National Linguistic Identity Sustainability in Multilingual Education Settings in Algeria: A Corpus-Based Analysis of Official Educational Discourse - selama, sid ali (LANGUAGE ART, 2025)
In the multicultural landscape of Algeria, where various linguistic groups coexist, the construction of national linguistic identity in a sustainable way within the framework of foreign languages education appears to be a multifaceted challenge. This corpus-based study meticulously investigates Algeria’s official educational discourse to unravel the intent of Algerian educational authorities in establishing a sustainable national linguistic identity among young language learners. Rooted in Critical Discourse Analysis, the study examines such pivotal documents as presidential speech and legislative texts, employing the "absences/presences technique." This method highlights not only what is present but also underscores the significance of what is absent in the official discourse. The research critically reevaluates fundamental assumptions about language functions and the objectives of foreign languages courses. By scrutinizing key documents, the study discerns the representation of national language –Arabic– within educational directives regarding foreign languages teaching/learning in Algeria. Analysis revealed a concerted effort in the official discourse to sustain national linguistic identity among learners, emphasizing attachment to Algerian values and cultural specificities. The documents underscore the importance of mastering Arabic, promoting Tamazight, and learning foreign languages, positioning the latter as a conduit for intercultural dialogue and understanding.